2018
DOI: 10.1038/s41398-018-0153-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the concentrations and size distributions of cell-free DNA in schizophrenia using fluorescence correlation spectroscopy

Abstract: Cell-free DNA (cfDNA), which is primarily released following cell death, has been described and developed to serve as an effective biomarker in autoimmune diseases which may share the pathogenesis with schizophrenia. In this study, we hypothesized and explored whether the concentrations and size distributions of cfDNA are abnormal in schizophrenia. A total of 65 patients with schizophrenia (SZ), 29 patients with mood disorders (MD) and 62 matched healthy controls (HC) were included in the study. Fluorescence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 28 publications
3
30
0
2
Order By: Relevance
“…In this study, we found that patients with schizophrenia had higher levels of cf-DNA in their blood than normal controls. The results of the study are consistent with those of Jiang [29] which testified that apoptosis exists in SZ patients and laid the foundation for the evaluation of clinical treatment effect. Our research is supplemented and expanded on this basis.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In this study, we found that patients with schizophrenia had higher levels of cf-DNA in their blood than normal controls. The results of the study are consistent with those of Jiang [29] which testified that apoptosis exists in SZ patients and laid the foundation for the evaluation of clinical treatment effect. Our research is supplemented and expanded on this basis.…”
Section: Discussionsupporting
confidence: 85%
“…1). SZ patients were divided into undifferentiated type (133), paranoid (11), acute schizophrenia-like psychosis (29), and other subtypes (2). The average concentration of cf-DNA in the different types were respectively 533.5 ng/ml (interquartlie range 237.1-1095.9 ng/ml), 849.9 ng/ml (interquartlie range 450.5-1378.6 ng/ml) and 1115.3 ng/ml (interquartlie range 167.1-1673.4 ng/ml).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations